Fentanyl Buccal Tablet: A New Breakthrough Pain Medication in Early Management of Severe Vaso‐Occlusive Crisis in Sickle Cell Disease. Issue 6 (26th May 2015) - De Franceschi, Lucia; Mura, Paolo; Schweiger, Vittorio; Vencato, Elisa; Quaglia, Francesca Maria; Delmonte, Letizia; Evangelista, Maurizio; Polati, Enrico; Olivieri, Oliviero; Finco, Gabriele
Abstract: Background: Sickle cell disease (SCD) is a worldwide distributed hereditary red cell disorder. The principal clinical manifestations of SCD are the chronic hemolytic anemia and the acute vaso‐occlusive crisis (VOCs), which are mainly characterized by ischemic/reperfusion tissue injury. Pain is the main symptom of VOCs, and its management is still a challenge for hematologists, requiring a multidisciplinary approach. Methods: We carried out a crossover study on adult SCD patients, who received two different types of multimodal analgesia during two separate severe VOCs with time interval between VOCs of at least 6 months. The first VOC episode was treated with ketorolac (0.86 mg/kg/day) and tramadol (7.2 mg/kg/day) (TK treatment). In the second VOC episode, fentanyl buccal tablet (FBT; 100 μg) was introduced in a single dose after three hours from the beginning of TK analgesia (TKF treatment). We focused on the first 24 hours of acute pain management. The primary efficacy measure was the time‐weighted‐sum of pain intensity differences (SPID24). The secondary efficacy measures included the pain intensity difference (PID), the total pain relief (TOTPAR), and the time‐wighted sum of anxiety (SAID24). Results: SPID24 was significantly higher in TKF than in TK treatment. All the secondary measures were significantly ameliorated in TKF compared to TK treatment, without major opioid side effects. Patients satisfaction was higher with TKF treatment than with TK one. Conclusions: We propose that VOCs might require breakthrough pain drug strategy as vaso‐occlusive phenomena and enhanced vasoconstriction promoting acute ischemic pain component exacerbate the continuous pain of VOCs. FBT might be a powerful and feasible tool in early management of acute pain during VOCs in emergency departments.